Los charrúas en la memoria nacional de Uruguay - Szilágyi Chebi, Mariá Elena (Acta Hispanica, 2015)
The Charrúas were an indigenousgroup who lived in the territories of the formerBanda Oriental (present Uruguay, the provincesof Entre Ríos, Santa Fe and Corrientes inArgentina, and Rio Grande do Sul, Brazil).Throughout the 18th century occurredcampaigns of “civilization” of the governors ofBuenos Aires against indigenous, resultinghundreds of deaths. In the first half of the 19thcentury the indigenous people, after theyfought in the armies for independence ofUruguay, were persecuted and sought toexterminate systematically the Charrúas. Thisfact is known as “the massacre of Salsipuedes”(1831). Nowadays several organizations havebeen created to rebuild, investigate and clarifythe facts, and assist all kinds of Charruancultural survival. This paper attempts to presentthe various ways in which the Charrúas survivein the national memory of Uruguayan society atpresent. At the same time, the role of theCharrúas in the formation of the nationalidentity of Uruguay is also examined.